TINDAKAN PRESERVASI KOLEKSI PADA PERPUSTAKAAN GOETHE-INSTITUT BANDUNG - Andi Kamila Ariani; Ute Lies Siti Khadijah; Samson CMS; Lutfi Khoerunnisa (Info Bibliotheca: Jurnal Perpustakaan dan Ilmu Informasi, 2022)
Preservation of library materials plays an important role in maintaining media and information that can be handed down to future generations and is necessary for long-term survival. The library as an institution that stores various information and knowledge, and the community, as information consumers, requires its existence, of course, expects that the library can store and share information and knowledge as needed. This is a challenge for library managers how information in the form of books, print or digital media can last a long time and not lose information or knowledge even though it has been a long time. Based on the above, the writer tries to write about the collection preservation action at the Goethe-Institut Bandung Library. The author employs a qualitative research methodology.Using a descriptive approach and gathering data techniques are carried out through the results of web analysis and literature studies. Besides that, the writer also uses interview, observation, and observation techniques, which are compiled to become a conclusion. The purpose of this study is to determine how far the preservation measures are carried out by the Goethe-Institut Bandung Library and what is being done in processing the library to ensure that the collection is safe from various factors. In relation to the issue of preservation interests, there are three terms that must be understood in terms of scope and differences in importance between the three, namely: preservation , conservation and restoration. Preservation is closely related to collection policy and dealing with preservation on a large scale is unlikely to be successful and can be developed without a clear statement of purpose. Existing collection policies will assist in determining preservation priorities that lead to the interests of the collection itself.